PENGUKURAN PRODUKTIVITAS SEKOLAH DI SMP KOTA MATARAM - Zulfikar, Ahmad; Afian, Tilal (Prodi Administrasi Pendidikan, Universitas Pendidikan Mandalika, 2021)
Abstract: Schools as educational organizations must always increase productivity with various innovations and achievements, should not stagnate in the comfort zone with low productivity, therefore it is necessary to measure school productivity for school self-evaluation as a reference in increasing school productivity. The purpose of this study was to describe the level of school productivity in the Mataram city junior high school. The method used in this study is a survey method with a quantitative approach, the population is 1620 respondents in 35 junior high schools consisting of principals, teachers and administrators, the sample used is 106 respondents, drawn using proportional stratified random sampling based on the sampling formula of solvin. The data collection technique used a questionnaire and then analyzed descriptive statistical data using the WMS (Weighted Means Scored) technique. The results of the measurement of school productivity at the Mataram City Middle School show that the school input dimension is in the very high category with a score of 4.37 while the school output is in the high category with a score of 4.25. Keywords: Measurement, School Productivity Abstrak: Sekolah sebagai organisasi pendidikan harus selalu meningkatkan produktivitas dengan berbagai inovasi dan prestasi, tidak boleh stagna pada zona nyaman dengan produktivitas rendah, maka dari itu diperlukan pengukuran produktivitas sekolah untuk evaluasi diri sekolah sebagai acuan dalam peningkatkan produktivitas sekolah. Tujuan dari penelitian Ini adalah untuk mengetahui gambaran tingkat produktivitas sekolah di SMP kota Mataram . Metode yang digunakan dalam penelitian ini adalah metode survey dengan pendekatan kuantitatif, populasinya adalah 1620 responden di 35 unit SMP yang terdiri dari kepala sekolah, guru dan tenaga administrator, sampel yang digunakan berjumlah 106 responden, ditarik dengan menggunkan proportional stratified random sampling berdasarkan rumus pengambilan sampel dari solvin. Teknik pengumpulan data menggunakan angket kemudian di lakukan analisis data statistik deskriptif dengan menggunakan teknik WMS (Weighted Means Scored). Hasil dari pengukuran produktivitas sekolah di SMP kota Mataram menunjukkan bahawa dimensi school input berada pada kategori sangat tinggi dengan skor 4,37 sedangkan school output berada pada kategori tinggi dengan skor 4,25. Kata kunci : Pengukuran, Produktivitas Sekolah